Pengaruh Profitabilitas, Leverage, Pertumbuhan Penjualan, Dan Capital Intensity Terhadap Agresivitas Pajak - Rajak, Raida; Suwito, Suwito (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The purpose of this study was to determine the effect of profitability, leverage, sales growth and capital intensity on the tax avoidance. The sampling method used is purposive sampling. The population in this study is the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) period 2016-2020. The population in this study was 176 observations (62 companies). The results showed that capital intensity has positive effect on the tax avoidance. Profitability has negative effect on the tax avoidance. While leverage and sales growth have no effect on tax avoidance.